Epidemiological Characteristics of Pertussis in Bantul District 2023: a Descriptive Study - Reza Firdaus, Muhammad; Aryanto, Samsu; Wiratama, Bayu Satria (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to determine the distribution of characteristics of pertussis patients in Bantul District. Method: A descriptive study using data on PERT-02 form at Bantul District Health Office in 2023 was conducted to observe demographics (age, gender, address), initially identified status and date of illness, transmission clusters obtained from investigation reports, and pertussis infection status. Diagnostic test for Pertussis was done using a nasopharyngeal swab and tested using Polymerase Chain Reaction (PCR). Proportion was used for univariate analysis and a spatial descriptive analysis was done to see the distribution of cases by sub-districts. Results: 130 people were identified as Pertussis suspects, of which 20 people (15.38%) were positive for Bordetella pertussis. Among cases, 16 people (80%) were male and 7 people (35%) were un-immunized infants of which 5 people (25%) were less than 2 months old and not yet immunized. There were 11 (55%) cases who were close contacts and eight people (72,7%) came from the school cluster. Symptoms in cases included coughing (68,4), whooping (31,6%), vomiting (26,3%), and apnoea (26,3%), and there were 6 people (30%) with no symptoms at all who were close contacts at baseline. Cases were spread across 7 sub-districts (41%) in Bantul district. The first case appeared in Mei 2023 and continued to increase until December 2023 with most cases occurring in August (25%) and November (25%). Conclusion: Males, un-immunized and school clusters were the dominant characteristics of pertussis patients in Bantul District. Cross-sectoral support such as schools needs to be improved because considering that most transmission occurs in schools, in addition to the knowledge of parents and teachers needs to be improved because many cases start as close contacts, which means prevention and control of pertussis has not been done optimally.